Formation constants in the ternary systems Co(H)-L-cysteine-adenine and Zn(II)-L-cysteine-(Adenine) 2 - (:unkn) unknown (My University, 2000)
In the present note, a potentiometric titration technique has been used to determine stability constants for the various complexes of Co(II) and Zn(II) with L-cysteine and from DNA bases i.e. Adenine. Stability constants of ternary systems have been evaluated by the method suggested by Irwing-Rossotti. In addition, the conditional constants were calculated as a function of pH. The maximum values of the conditional formation constants were found to be in accordance with the mixed-ligand complex formation constants in a given pH region. In addition, the mole fractions of different species from mixed complexes were calculated by means of formation constants. The values of stability constants of mixed-ligand complexes at 25°C are as follows: logK=9.50 for Co(II)-L-cysteine-adenine; logK 1=6.85 and logK 2=6.00 for Zn(II)-L-cysteine-adenine 2. The ionic strength was kept constant at 1=0.20 with NaClO 4.
Keywords: Adenine; Cobalt(II) and zinc(II) complexes; L-cysteine; Mixed complex; Stability constants